Counseling on the Hand Hygiene Process as an Effort to Prevent Microbial Transmission and Covid-19 in the School Environment for Students of SMA Negeri 3 Denpasar - Wulansari, Nadya Treesna; Padmiswari, Anak Agung Istri Mas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institute Teknologi dan Kesehatan (ITEKES) Bali, 2021)
This outbreak of the corona virus requires integrated handling by involving all components of society to deal with Covid-19, which is a world pandemic. This virus is easily transmitted to other people through droplets when talking or someone coughing. One of the efforts that can be done is to apply a clean lifestyle, namely Hand Hygiene. Hand hygiene is one of the easiest efforts to do starting from yourself. One way to introduce to the community, especially school children, about good and correct hand hygiene procedures is to provide counselling and demonstrations. Education about the understanding of school-age children regarding the importance of hand hygiene needs to be carried out more deeply. Good and correct hand hygiene can reduce the number of microorganisms on hands and prevent the spread of Covid-19 in the school environment. Implementation of activities carried out by conducting counselling and demonstration of hand hygiene. Students are given pre-test first and post-test after counselling and demonstration. The results show that there is an effect of providing counselling regarding the application of Hand Hygiene techniques to students' knowledge. This activity shows an increase in students' knowledge after being given counselling and demonstrations on the application of Hand Hygiene.